The role of mitochondria in yeast programmed cell death - Guaragnella, Nicoletta; Ždralević, Maša; Antonacci, Lucia; Passarella, Salvatore; Marra, Ersilia; Giannattasio, Sergio (Frontiers in Oncology, 2012)
Mammalian apoptosis and yeast programmed cell death (PCD) share a variety of features including ROS production, protease activity and a major role played by mitochondria. In view of this, and of the distinctive characteristics differentiating yeast and multicellular organism PCD, the mitochondrial contribution to cell death in the genetically tractable yeast Saccharomyces cerevisiae has been intensively investigated. In this mini-review we report whether and how yeast mitochondrial function and proteins belonging to oxidative phosphorylation, protein trafficking into and out of mitochondria, and mitochondrial dynamics, play a role in PCD. Since in PCD many processes take place over time, emphasis will be placed on an experimental model based on acetic acid induced PCD (AA-PCD) which has the unique feature of having been investigated as a function of time. As will be described there are at least two AA-PCD pathways each with a multifaceted role played by mitochondrial components, in particular by cytochrome c.